Mechanical synthesis and rapid consolidation of a nanocrystalline Cu-Al2O3 composite by high frequency induction heated sintering - Shon, In-Jin; Lee, Jin-Yeoung; Nam, Kee-Seok; Moon, Byung-Moon; Lee, Dong-Mok (Electronic materials letters, 2009)
Cu and Al 2 O 3 nanopowders were synthesized from 3CuO and 2Al by high energy ball milling. The powder sizes of Cu and Al 2 O 3 were 14 nm and 133 nm, respectively. A dense nanocrystalline 3Cu-Al 2 O 3 composite was consolidated by a high frequency induction heated sintering method within 2 minutes from the mechanically synthesized powders. The average hardness and fracture toughness values of the nanostuctured 3Cu-Al 2 O 3 composite were 520 kg/mm 2 and 5 Mpa·m 1/2 , respectively.